2022
DOI: 10.30605/jsgp.5.3.2022.1514
|View full text |Cite
|
Sign up to set email alerts
|

Junior High School Students’ Perception of Using Mobile Application to Learn English Pronunciation

Abstract: Technology into their teaching as well as how to assist students in making use of resources such as media and the internet to improve their learning of all four skills, particularly teaching and learning English pronunciation. Students are gradually motivated by their personal learning needs, including those that arise from greater mobility and traveling activities, during the initial period of mobile learning. Mobile learning, particularly Mobile Assisted Language Learning (MALL), has become essential tools i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For two weeks, students were involved in mobile learning focusing on physics subject matter. The results of this research conclude that students in this area receive mobile learning well (Winzky & Aswir, 2022).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…For two weeks, students were involved in mobile learning focusing on physics subject matter. The results of this research conclude that students in this area receive mobile learning well (Winzky & Aswir, 2022).…”
Section: Introductionmentioning
confidence: 61%
“…Another study (Winzky & Aswir, 2022) evaluated how first-year students at an Islamic junior high school in Indonesia responded to using mobile applications to improve their English pronunciation. The results revealed that students gave a positive view towards the use of mobile applications in learning English pronunciation, which could contribute to improving their English pronunciation skills.…”
Section: Introductionmentioning
confidence: 99%
“…Conducted in a Senior High School that follows the K-13 curriculum and is transitioning to the Merdeka curriculum for certain grades, this research found that while specific lessons on diphthongs are not explicitly taught, pronunciation is integrated throughout the English subject for eighth and ninth grades. The curriculum mandates that students must correctly pronounce words in vocabulary sections, grammar points (tenses), and reading passages (Hidyatulloh, 2023;Winzky & Aswir, 2022).…”
Section: Methodsmentioning
confidence: 99%